2002
DOI: 10.1001/archinte.162.10.1095
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Function in the Human Immunodeficiency Virus–Infected Patient

Abstract: Although clinical manifestations of adrenal dysfunction are uncommon in patients infected with human immunodeficiency virus (HIV), subclinical functional abnormalities of the hypothalamic-pituitary-adrenal axis are frequent. Patients infected with HIV usually have higher basal serum cortisol and lower serum dehydroepiandrosterone concentrations than HIV-seronegative individuals. This imbalance has been related to progression of the infection by inducing a shift from T(H)1 to T(H)2 immunologic responses. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 49 publications
(60 reference statements)
0
37
0
Order By: Relevance
“…Our findings show similar results since the mHDS also measures declarative verbal memory. Glucocorticoid (GC) levels (reflected by cortisol levels in humans) are elevated for prolonged periods in HIV-1 infection [21] . Given the close significant relation between cortisol response to stress, HIV serostatus and cognitive function, the findings from the present study present suggestive parallels to these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show similar results since the mHDS also measures declarative verbal memory. Glucocorticoid (GC) levels (reflected by cortisol levels in humans) are elevated for prolonged periods in HIV-1 infection [21] . Given the close significant relation between cortisol response to stress, HIV serostatus and cognitive function, the findings from the present study present suggestive parallels to these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality could be further avoided by monitoring those with advanced disease as they start ART, and it raises the possibility that early mortality could also be due to undiagnosed opportunistic infections, nutritional deficiencies, or severe immune reconstitution inflammatory syndrome, although there is no direct evidence to support these possible reasons. [23][24][25] This study showed reduced early mortality as patients who attended the clinic were diagnosed quickly and were counselled to start ART before they become wasted and anemic. 6 Though the stigma associated with the disease prevent patients from seeking early treatment, the free provision of drugs by government ART centres has encouraged people to seek medical attention earlier, as has been observed in the United States and other developed countries.…”
Section: Discussionmentioning
confidence: 87%
“…However, chronic stress causes cortisol overproduction, resulting in damaging effects. There is evidence that elevated cortisol levels or impaired cortisol regulation increases atherosclerosis [127], hypertension [128], cancer [129], obesity [130], osteoporosis [131], immunodeficiency [132], hyperlipidemia [133,134], depression [135], some anxiety [136] and aggression-related disorders, such as drug abuse and other addictive disorders [137]. TM practice has been shown to produce a healthy cortisol profile of lower baseline levels and a more robust cortisol response to acute stress.…”
Section: Stress Reduction Cortisol and Cvd Riskmentioning
confidence: 99%